OPTIMIZATION ANALYSIS ON GEAR AND RACK FOR JACKING-SYSTEM OF JACK-UP PLATFORM - LV Tao; XU ChangHang; CHEN GuoMing; LI LinLin (Jixie qiangdu)
The load bearing capacity of gear and rack system is a very important safety factor for the jack-up offshore platform,so there is an important engineering significant to improve and analyze gear and rack system to increase it. According to the main reason for the failure of the rack and gear,different fillet radius features on both ends of the rack and gear and rack modification were builded,and the effects of the different fillet radius and modification coefficient to the carring capacity of the rack were analyzed by finite element analysis. The results showed that the degree of stress concentration dropped significantly with chamfers on the rack,and with the increase of the fillet radius,the contact stress on the both ends of the rack deceases first then increases to a certain extent. Modification coefficient has a major influence on the maximum contact stress of gear,but has less impact on the racks’. When the fillet radius is in the range of 2 mm 6 mm,and the modification coefficient is 0. 5,the contact stress and bending stress of gear and rack system can get great improvements,and the load bearing capacity of gear and rack system is increased in the meantime.